Sustaining Work-Life Balance of Teachers During the New Normal (American Journal of Interdisciplinary Research and Innovation, 2023)
This study explored the lived experiences of the public-school primary teachers and their ways in sustaining work-life balance during the COVID-19 pandemic. The research employed a qualitative research design of phenomenology. The responses were analyzed following the steps of Colaizzi’s descriptive phenomenological method. The researcher thoroughly reviewed the transcripts of interviews and used a coding sheet in organizing the codes. The process was repetitively conducted and was evaluated by the researcher’s rater and adviser prior to finalizing the main themes relevant to the phenomenon under study. The following were the findings of the study: (1) There had been changes in the workload of teachers during this pandemic; these are: (a) additional workloads due to; instructional planning and preparation; feedbacking and monitoring system, attending webinars, and online meetings, (b) irregular working hours, (c) ICT Capabilities and (d) Internet/Wifi Access (2) The pandemic impacted teachers’ constructive experiences because they had opportunity to grow and learn and also it impacted their adverse experiences because it compromised family time and it made them feel stress and anxious. (3) Teachers are significantly challenged by overlapping of activities, limited gadgets and technology, evaluating learning outcomes, fear of acquiring the virus, and engaging pupils into active learning. (4) Teachers coping techniques or interventions prior to the difficulties and challenges are time management and prioritization, embracing changes, flexibility and adaptability, and employing break time. (5) The values and faith strengthened during this pandemic are resiliency, self-appreciation, nurturing spiritually and creativity.